Urban water supply and sanitation in Mongolia: A description of the political, legal, and institutional framework - Katja Sigel (Helmholtz-Zentrum für Umweltforschung (UFZ), 2012)
The lack of adequate water supply and sanitation services is a major issue related to sustainable development in many parts of the developing world. This also holds for Mongolia. Current data suggests that Mongolia may not meet the Millennium Development Goal 7, target 7c to halve the proportion of people without sustainable access to safe drinking water and basic sanitation by 2015. This mostly applies to peri-urban ger areas where people live in gers - the traditional Mongolian portable felt tent - and/or in simple, detached houses. This report analyses the political, legal and institutional framework for improving urban water supply and sanitation in Mongolia. A special focus is placed on domestic consumers, notably the peri-urban poor living in the ger areas of large cities such as Ulaanbaatar, Darkhan and Erdenet. All administrative levels are included in the assessment. The report shows that a variety of policies, programmes, laws and regulations concerning aspects of the water supply and sanitation sector exist, but they are not harmonised and there are significant gaps. The specific problems of peri-urban ger areas are not normally addressed in these policy documents. Some authors argue that the problem is not so much the lack of policies and laws but a lack of capability to implement them and the absence of clear institutional responsibility.
Keywords: 330; water supply; sanitation; Mongolia; peri-urban; policies; laws; institutions; enabling environment; Wasserversorgung; Kanalisation; Stadtregion; Institutionalismus; Mongolei